Cardiac Drugs Requirement during Off-Pump Coronary Artery Bypass (OPCAB) Surgery- A Comparison between Combined High Thoracic Epidural Anaesthesia (HTEA) with GA and GA Alone - Azad, SI; Beg, AK; Chowdhury, AYFE (Cardiovascular Journal, 2010)
Background: During off pump coronary artery bypass surgery (OPCAB) to provide adequate myocardial protection cardiac anaesthesiologist frequently needs to use various pharmacological intervention rather than physiological manipulation. This is challenging to overcome the adverse effects of the various drugs. During the past few years, high thoracic epidural anaesthesia (HTEA) as an adjunct to general anaesthesia has become more popular and has been shown to be potentially beneficial in patients with coronary diseases. It provides good protection from stress response, ensures hemodynamic stability, improves distribution of coronary blood flow and reduce demand for oxygen and perioperative arrhythmia. Objective: This study has been undertaken with a view to compare the requirement of intraoperative cardiac drugs between HTEA with General Anaesthesia(GA) and GA alone. Methods: Prospective, randomized case control study was undertaken in sixty patients, without having left main coronary disease, left ventreicular ejection fraction <35% or contraindication of regional anaesthesia scheduled for OPCAB. They were divided into two groups, thirty in each group. Group A patients received GA alone and group B patients received high thoracic epidural anaesthesia with GA. Requirement of drugs (antiarrhythmic, inotropes, vasoconstrictor, vasodilators,Esmolol e.g.) during operation were recorded. Results: Dopamine was needed in 27(90.0%)patients in group A and 11(36.7%) patients in group B, adrenaline was used in 15(50.0%)patients in group A and 4(13.3%) in group B; Dobutamine was used only in 5(15.0%) patients in group A and ephedrine was required only in 2(5.0%) in group B. Regarding the Antiarrhythmic drugs, Lignocanie, Amiodarone and DC Shock was required only in 17(55.0%), 12(40.0%) and 5(15.0%) patients respectively only in group A. In vasodilators group, Nitropruside was used in 5(15.0%) and 1(3.3%) patients in group A and group B respectively. Esmolol was used in 17(55.0%) patients in group A and 1(3.3%) in group B. Significant (p<0.05) difference were found in use of all drugs between two groups except Ephedrine and Nitropruside. Conclusion: The anaesthetic technique HTEA with GA required minimum intra operative cardiac drugs than GA only. Key words: Cardiac drug; HTEA; General Anaesthesia; OPCAB. DOI: 10.3329/cardio.v3i1.6420 Cardiovasc. j. 2010; 3(1): 7-10